Simple synthesis of sandalwood odorant rac‐Osyrol® and its ethoxy homologue. (28th September 2015) - Parthasarathy, Rajasekaran; Sulochana, Nagarajan
Abstract: rac ‐Osyrol ® (3, 7‐dimethyl‐7‐methoxyoctane‐2‐ol), a commercially important sandalwood odorant has been prepared from dihydromyrcene in three steps. The key steps in the synthesis are the epoxidation of terminal double bond using urea hydrogen peroxide (UHP) and regioselective reduction of epoxide using Vitride ® . The same strategy has been applied to the synthesis of its ethoxy homologue. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A commercially viable process was developed for sandalwood odourant rac ‐Osyrol ® and its ethoxy homologue starting from dihydromyrcene by terminal epoxidation using UHP followed by regioselective reduction using Vitride ® .